Numerical simulation for liquid sloshing with baffle by the CLSVOF/IB method. (15th August 2022) - Yu, C.H.; Wu, T.C.; An, R.D.; Li, Y.L.
Abstract: The liquid sloshing problem in a partially filled rectangular tank is numerically investigated by a Coupled Level Set and Volume Of Fluid (CLSVOF) method. In the present CLSVOF method, the Level Set (LS) equation needs to be solved to advect the LS function for calculating interface curvature; the re-distancing equation is also taken into account for the LS function being maintained as a distance function. For capturing the interface, the Tangent of Hyperbola for INterface Capturing (THINC) scheme with Weighted Linear Interface Calculation (WLIC) is implemented to advect the Volume of Fluid (VOF) function. To preserve mass conservation, the interface reconstruction procedure needs to be carried out on the basis of the connection between LS and VOF functions. Rectangular and prismatic tanks are used to validate the accuracy and mass conservation of the present CLSVOF method. Then, further simulations of the problem of partially filled liquid sloshing with baffle considered are conducted by combining the CLSVOF method and the Immersed Boundary (IB) method. Finally, the influence of different baffle lengths on the slapping pressure and free-surface is discussed.